2007
DOI: 10.1021/jp073731v
|View full text |Cite
|
Sign up to set email alerts
|

Adipic and Malonic Acid Aqueous Solutions:  Surface Tensions and Saturation Vapor Pressures

Abstract: The surface tension of adipic aqueous solutions was measured as a function of temperature (T=278-313 K) and adipic acid mole fraction (X=0.000-0.003) using the Wilhelmy plate method. A parametrization fitted to these data is presented. The evaporation rates of binary water-malonic and water-adipic acid droplets were measured with a TDMA technique at different temperatures (T=293-300 K) and relative humidities (58-80%), and the saturation vapor pressures of subcooled liquid malonic and adipic acids were derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
74
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 55 publications
13
74
1
Order By: Relevance
“…The optimal parameters for azelaic acid appear to be in the appropriate range for P o but with slightly lower H than the available literature. Optimal parameters for malonic acid (Figure 7c) agree to within uncertainty with Riipinen et al (2007). Results for succinic acid (Figure 7f) appear consistent with estimates of solid P o from various literature sources.…”
Section: Tablesupporting
confidence: 79%
“…The optimal parameters for azelaic acid appear to be in the appropriate range for P o but with slightly lower H than the available literature. Optimal parameters for malonic acid (Figure 7c) agree to within uncertainty with Riipinen et al (2007). Results for succinic acid (Figure 7f) appear consistent with estimates of solid P o from various literature sources.…”
Section: Tablesupporting
confidence: 79%
“…Typical values for the pure component liquidstate surface tensions of low-polarity to moderately polar multifunctional organic compounds range from ~20 to ~50 mN m -1 in the temperature range from 288 to 298 K 73 . For example, at 298 K, surface tensions of 37, 27, and 26 mN m -1 were measured for formic acid, acetic acid, and propionic acid, respectively 74 ; ~35 mN m -1 was determined for adipic acid 75 , ~32 mN m -1 for oleic acid 76 and a range of 20 to 30 mN m -1 was inferred for a mixture of multifunctional organic compounds from α-pinene oxidation 77 . For simplicity and in reasonable agreement with the measured range of pure-component surface tensions, we use an average value of = 30 mN m -1 for all organic compounds considered.…”
Section: Modelling Approach For Effective Surface Tensionmentioning
confidence: 99%
“…Some of the estimation methods can give errors in vapour pressure of several orders of magnitude for multifunctional compounds at ambient temperatures Booth et al, 2010). There are several experimental methods available for very-low vapour pressure measurements including Tandem Differential Mobility Analysis (TDMA) (Bilde and Pandis, 2001;Bilde et al, 2003;Mønster et al, 2004;Riipinen et al, 2007;Froesch et al, 2010;Salo et al, 2010), White light resonance spectroscopy (Zardini et al, 2006), Temperature Programmed Desorption (TPD) (Cappa et al, 2007;Chattopadhyay and Zieman, 2005), Electrodynamic Balance (EDB) (Pope et al, 2010;Soonsin et al, 2010), Optical tweezers (Pope et al, 2010), Knudsen…”
Section: Introductionmentioning
confidence: 99%
“…656 A. M. Booth et al: Liquid vapour pressures of cyclic aliphatic dicarboxylic acids Effusion Mass-loss (Riberio da Silva et al, 1999Silva et al, , 2001 and Knudsen Effusion Mass Spectrometry (KEMS) (Booth et al, 2009). They have been previously used to study straight chain (Riberio da Silva et al, 1999;Bilde et al, 2003;Chattopadhyay and Zieman 2005;Zardini et al, 2006;Riipinen et al, 2007;Cappa et al, 2007;Salo et al, 2010;Pope et al, 2010;Soonsin et al, 2010), branched (Riberio da Silva et al, 2001;Mønster et al, 2004;Booth et al, 2010), cyclic (Bilde and Pandis, 2001) and substituted (Chattopadhyay and Zieman 2005;Froesch 2010, Booth et al, 2010) dicarboxylic acids which have been identified in the atmosphere (Hallquist et al, 2009;Kawamura et al, 1996;Sempere and Kawamura, 1994;Gao et al, 2004;Kawamura et al, 2005) as likely products of VOC oxidation. These dicarboxylic acids are solids at room temperature and pressure; however, current gas/particle partitioning models use the sub-cooled liquid reference state, as do activity models (Booth et al, 2010;Riipinen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%